Invasão biológica por Sesbania virgata (CAV.) PERS. na Paraíba, Brasil: biologia reprodutiva, ecofisiologia de sementes e estrutura populacional. - Souza, Vênia Camelo de (2012)
Scientific knowledge about the invasive taxon Sesbania virgata in the Northeast Brazil is still very incipient, therefore this research aimed to know this species biological invasion process, through studies of reproductive biology, seed ecophysiology and population structure. Field experiments were carried out with Sesbania virgata occurring population in the agreste of State of Paraíba, and the Paraíba river banks. Experiments were also carried out in the Plant Ecology and Seed Analysis Laboratories of the Agrarian Sciences Center of the Paraíba Federal University at Areia - PB, and in the Campus IV, Rio Tinto – PB. This research was structured in seven chapters according to the following approach: Chapter 1 – Plant biological invasion background; Chapter 2 – Phenology of the invasive species S. virgata in the county of Areia-PB; Chapter 3 – S. virgata flower biology: an invasive species in the agreste of State of Paraíba; Chapters 4, 5 and 6 – S. virgata seed dormancy, seed longevity under different storage and abiotic stress conditions; Chapter 7 – Structural analysis of a S.virgata population as invasive species of the Caatinga in the Paraíba River banks. S.virgata invasion strategies and proves that it is an aggressive invasive species in the studied environments.